A novel series of chlorinated plastoquinone analogs: Design, synthesis, and evaluation of anticancer activity. (2nd January 2020) - Bayrak, Nilüfer; Yıldırım, Hatice; Yıldız, Mahmut; Radwan, Mohamed O.; Otsuka, Masami; Fujita, Mikako; Ciftci, Halil I.; Tuyun, Amaç Fatih
Abstract: Herein, we report the synthesis and cytotoxic effects of novel chlorinated plastoquinone analogs (ABQ1–17 ) against different leukemic cells. Compounds ABQ3, ABQ11, and ABQ12 demonstrated a pronounced antiproliferative effect against chronic myelogenous leukemia (CML) K562 cell line with IC50 values of 0.82 ± 0.07, 0.28 ± 0.03, and 0.98 ± 0.22 μM, respectively. Among them, ABQ11 showed approximately three times higher selectivity than imatinib on CML. ABQ11 ‐treated CML cells induced significant apoptosis at low concentration. Inhibitory effect of ABQ11 against eight different tyrosine kinases, including ABL1, was investigated. ABQ11 inhibited ABL1 with IC50 value of 13.12 ± 1.71 μM, indicating that the moderate inhibition of ABL1 kinase is just an in‐part mechanism of its outstanding cellular activity. Molecular docking of ABQ11 into ABL1 kinase ATP‐binding pocket revealed the formation of some key interactions. Furthermore, DNA cleavage assay showed that ABQ11 strongly disintegrated DNA at 1 μM concentration in the presence of iron (II) complex system, assuming that the major mechanism for the anticancer effects of ABQ11 is DNA cleavage. In silico ADMET prediction revealed that ABQ11 is a drug‐like small molecule with a favorable safety profile. Taken together, ABQ11 is a potential antiproliferative hit compound that exhibits unique cytotoxic activity distinct from imatinib. Abstract : The most potent analog was found to understand apoptotic induction, kinase profiling, molecular docking, DNA cleavage, and safety profile analysis.